Plasma modification of 3-D biodegradable scaffolds to improve surface wettability; Energy Fluxes and Radiation Effects (EFRE-2016) - Syromotina D. S. Dina Sergeevna; Zviagin A. Andrei; Surmenev R. A. Roman Anatolievich; Surmeneva M. A. Maria Alexandrovna; Oehr C. Christian (2016, 2016)
Title screen